Evaluation and treatment of moulding sand for green sand moulding process - 212072 Norhaswani Kasim (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006